Development of fruit-flavored nipa (Nypa fruticans Wurmb.) alcoholic drinks - Flores, Noeme D. (2011)
This study was conducted to develop a fruit-flavored alcoholic drinks from nipa (Nypa fruticans Wurmb.) vodka by infusing some of the abundant fruits of Mindanao. In this study, guyabano and pomelo were utilized. Per fruit, three formulations were prepared with varying fruit percentage to vodka (15%, 30%, 45%) and period of infusion (3,8 and 14 days). These samples were subjected to a series of preference ranking tests to determine the final formulation. Friedman's test results showed that for guyabano, the vodka that contained 45% fruit and infused for 8 days was the most preferred formulation. While the vodka with 15% fruit and infused for 6 days was the most preferred for pomelo. In the consumer acceptability test of these final products, results of the Sign test indicated that their sensory attributes which include the appearance, flavor, aroma, astringency and overall acceptability were accpatble to its potential consumers. The physicochemical characteristics of the fianl products were as follows : for guyabano flavor, the alcohol content is 5%, pH is 4.3073, TSS is 10,73 Brix and TTA (citric acid) is 0.410%; for pomelo flavor, the alcohol content is 20%, pH is 4.0550, TSS is 9.033 Brix and 0.266% for TTa (citric acid).
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2011
Keywords: Nipa vodka; Guyabano; Pomelo; Preference Ranking Test; Consum